CDK4/6 Inhibitors: Game Changers in the Management of Hormone Receptor–Positive Advanced Breast Cancer? - Shah, Mirat (Oncology (Williston Park), 2018)
The cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors palbociclib, ribociclib, and abemaciclib are rapidly transforming the care of patients with hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative (HR+/HER2−) advanced breast cancer. Current clinical questions include how to choose among these agents and how to sequence them with other therapies. Areas of active inquiry include identifying predictive biomarkers for CDK4/6 inhibitors, deciding whether to continue CDK4/6 inhibitors after disease progression, creating novel treatment combinations, and expanding use beyond HR+/HER2− advanced breast cancer. Here, we review the current use of and potential next directions for CDK4/6 inhibitors in the treatment of patients with HR+ breast cancer.